Climate change, agriculture, and adaptation options for Colombia - Boshell, Francisco; Thomas, Timothy S.; Nazareth, Vijay; Cenacchi, Nicola (International Food Policy Research Institute, 2019)
Climate change is already affecting the global economy between catastrophic losses from extreme weather events to the subtler losses in agricultural productivity. In the decades to come, the effects of climate change will increase. Now is the time for policymakers to better understand the potential impacts of climate change on agriculture so that they might make appropriate investments and implement effective policies to help farmers better adapt to climate change. This discussion paper uses multiple models to assess the impact of climate change on agriculture in Colombia up to 2050. Some of the analysis is at a very fine geographic resolution, while other is at the national level. The biophysical models used here project modest impacts of climate change on rice and maize, at a cost of around 10 percent of national production. Losses to sugarcane are projected to be much higher, at around 28 percent. Recommendations are made for how policymakers might reduce the losses to these crops and others included in the analysis presented in this paper.